CALCULATION OF THE STRESS-STRAIN STATE OF PIPELINES SUBJECT TO GROOVE WEAR BY THE FINITE ELEMENT METHOD - Timur Sultanmagomedov; Ramil Bakhtizin; Sultanmagomed Sultanmagomedov (Izvestiâ Tomskogo politehničeskogo universiteta. Inžiniring georesursov, 2023)
Link for citation: Sultanmagomedov T.S., Khalikov T.M., Bakhtizin R.N., Sultanmagomedov S.M. Calculation of the stress-strain state of pipelines subject to groove wear by the finite element method. Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 6, рр.151-162. In Rus. The relevance of the study is dictated by the obsolescence of the field pipelines used, which means the need to improve the quality of field and desk work on their diagnostics and industrial safety expertise. The paper considers the possibility of applying numerical analysis of the stress-strain state of a pipeline subject to groove wear using the finite element method. For this purpose, a model of a pipeline with a defect is created and the formation of a crack is considered. The flat and volumetric problem statements are considered, the analysis of available studies is carried out. The purpose of the research is to study the possibility of using finite element method to simulate the development of defects in pipelines. For the widespread introduction of finite element method for in-house processing during industrial safety expertise, it is necessary to justify the need for its use. For this purpose, the problem of determining the stress-strain state of a pipeline with groove wear, with subsequent verification of the results, is considered. Objects: finite element analysis of field pipelines subject to metal loss defects. Methods: mathematical modeling, experimental methods, methods of theoretical mechanics. Results. A mechanical theoretical calculation of stresses in the cross section of a pipeline subject to stream corrosion was performed; the calculation results are compared with the results of experiments by other authors. Based on the results of calculations obtained on a theoretical model, a method for assessing the technical condition of a pipeline with rivulet corrosion is proposed, which consists in introducing a crack into the original geometry in places with critical stresses and subsequent analysis of the structure. A mechanical theoretical calculation of stresses arising in the section of a defective section of the pipeline during its preventive rotation is performed.